2019
DOI: 10.1108/ssrp-11-2018-0041
|View full text |Cite
|
Sign up to set email alerts
|

Elementary classroom libraries and social studies trade books

Abstract: Purpose Standards and policy changes in K-12 education have created the unintended consequence of reducing instructional time spent on social studies content. This limited time devoted to social studies presumably has led to more integrated social studies and literacy instruction. The purpose of this paper is to document the types of high-quality social studies children’s books found in classroom libraries across five states. Design/methodology/approach In the present mixed methods study, the researchers uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This is not enough, as the quality and quantity of books available in classroom libraries vary greatly ( Hodges et al , 2019). Furthermore, in an analysis of 60 classroom libraries, Hodges et al (2019a, b) found that very few award-winning informational texts (as define by national educational organizations) are actually present in classrooms. Existing research does outline best practices for incorporating informational texts into the classroom (Bradley and Donovan, 2010); however, it does not address the challenge of actually providing students access to quality, relevant and suitable informational texts.…”
Section: Related Workmentioning
confidence: 99%
“…This is not enough, as the quality and quantity of books available in classroom libraries vary greatly ( Hodges et al , 2019). Furthermore, in an analysis of 60 classroom libraries, Hodges et al (2019a, b) found that very few award-winning informational texts (as define by national educational organizations) are actually present in classrooms. Existing research does outline best practices for incorporating informational texts into the classroom (Bradley and Donovan, 2010); however, it does not address the challenge of actually providing students access to quality, relevant and suitable informational texts.…”
Section: Related Workmentioning
confidence: 99%
“…Since the early 1970s, teachers were reduced teaching time devoted to social studies as they increasingly focus on reading and mathematics, and this trend continued until the 1980s (Hodges et al, 2019). The decrease in interest in social studies education over time has started with the acceleration of standards and test movements in mathematics, especially since 1991 in the world.…”
Section: Introductionmentioning
confidence: 99%